Peran Sumber Daya Manusia Dalam Meningkatkan Pembangunan Kesejahteraan Masyarakat - Yakobus Mirin; wayrohi meilvidiri (Faculty Of Economics and Business, Musamus University, 2022)
ABSTRACT This study aims to determine the role of human resources in improving the development of community welfare in Bokem Village, Merauke District, Merauke Regency. The sample used was 11 informants, using a qualitative approach to analyze data related to the object of research. While the data collection techniques used include interviews and observations. The results of the study through interviews showed that the role of the quality of human resources in Bokem Village, almost 32% of informants said it was very good, as well as for the role of formal and non-formal education development, almost 36% of informants said the government had implemented formal and non-formal education programs by providing trainings. to the community starting from 2015-2016, the aim is to encourage the development of human resources, especially for people who have limited education and knowledge in theory and practice in the field so that they can understand and develop themselves independently, according to their personal power of thought and abilities. The results of the research through interviews showed that the role of infrastructure development in Bokem Village, almost 35% of informants said it was very good, this was seen from the provision of decent housing assistance for the community and providing public facilities in Bokem Village. it's just that the obstacle is the construction of road infrastructure connecting Bokem Village to the city which is very worrying, so this is also one of the obstacles to the economy for the people of Bokem Village. However, the government has never carried out the development role in the field of fisheries, such as providing fishing gear and providing training to the community related to the fishery sector. If the development role in the field of animal husbandry and agriculture has been very good, this can be seen from the provision of livestock, as well as the provision of fertilizers and heavy equipment to the community so that they can support the business processes of the corporate community, so that the community can feel welfare. Meanwhile, the role of development in the fields of education and health has not been going well until now, this is due to the lack of discipline for teachers and medical personnel in teaching positions and health services to the community in Bokem Village. Keywords: Human Resources, Community Welfare Development